Rural road networks and their roles in alleviating poverty among local communities in Bau-Lundu areas Kuching division - Jong, Kiam Leong (2005)
Rural development is of high priority for Sarawak, as majority of the population, and mostly of the poor, is living in the rural areas. However, the progress and development programs to these rural areas are always impeded by the lack of proper infrastructure and amenities like efficient road network for transportation and communication. The standard of living for the rural poor, who comprises of mostly the local indigenous communities, are also far from desired when compared with the quality of life of the urban populations. Economic linkages between transport and poverty are prominent in easing the burden of poverty. It has been observed that efficient transport will reduce poverty, mainly by increasing economic efficiency. As such, efficient transport networks and rural roads are closely related to the living condition of the poorer rural populations. The contributions of transport operations to poverty alleviation include the increase in the efficiency of resource allocation, the market performance, the flexibility of adjustments and the fostering of economic growth. Poverty are also closely linked to the accessibility of amenities like schools, health clinics, access to economic, employment and social opportunities. As such, there is a need to strengthen the direct role of road networks, accessibilities and transport interventions in poverty alleviations.